PENGARUH MACAM MULSA DAN DOSIS PUPUK KANDANG AYAM TERHADAP HASIL TANAMAN SELADA (Lactuca sativa, L.) VAR. NEW GRAND RAPID - Mia Herumia; Gembong Haryono; Yulia Eko Susilowati (Universitas Tidar, 2017)
The research on the effect of mulch kinds and the effect of chiken manure doses to the lettuce yield (Lactuca sativa, L.) var New Grand Rapid. Experiment conducted in August until October 2016. Location of experiment in Dukuhan, Sumber, Dukuh, Magelang. The latitude is 663 m. The soils regosol with pH 6,3. The research method used factorial experiment (3x4) arranged in a randomized complete block design with three blocks. The first factor is mulch kind, transparant plastic mulch, black silver plastic mulch, black plastic mulch. The second factor is chicken manure dose, 5 ton/ha, 10 ton/ha, 15 ton/ha, and 20 ton/ha.The result of the research shows that the use of black plastic mulch and black silver plastic mulch increase the height of plant, number of leaves, weight of fresh leaves and weight of dry leaves. Increasing chicken manure dose can increase height of plant, number of leaves, weight of fresh leaves, weight of dry leaves, weight of fresh root, and weight of dry root. The combination of mulch kind and chicken manure dose responded the same in all observation parameter.